Exercise-Induced Cardiac Fatigue in Soldiers Assessed by Echocardiography - Charton, Marion; Kervio, Gäelle; Matelot, David; Lachard, Thibault; Galli, Elena; Donal, Erwan; Carré, François; Le Douairon Lahaye, Solène; Schnell, Frédéric (Frontiers in Cardiovascular Medicine, 2021)
Background: Echocardiographic signs of exercise-induced cardiac fatigue (EICF) have been described after strenuous endurance exercise. Nevertheless, few data are available on the effects of repeated strenuous exercise, especially when associated with other constraints as sleep deprivation or mental stress which occur during military selection boot camps. Furthermore, we aimed to study the influence of experience and training level on potential EICF signs. Methods: Two groups of trained soldiers were included, elite soldiers from the French Navy Special Forces (elite; n=20) and non-elite officer cadets from a French military academy (non-elite; n=38). All underwent echocardiography before and immediately after exposure to several days of uninterrupted intense exercise during their selection boot camps. Changes in myocardial morphology and function of the 4 cardiac chambers were assessed. Results: Exercise-induced decrease in right and left atrial and ventricular functions were demonstrated with 2D-strain parameters in both groups. Indeed, both atrial reservoir strain, RV and LV longitudinal strain and LV global constructive work were altered. Increase in LV mechanical dispersion assessed by 2D-strain and alteration of conventional parameters of diastolic function (increase in E/e’ and decrease in e’) were solely observed in the non-elite group. Conventional parameters of LV and RV systolic function (LVEF, RVFAC, TAPSE, s mitral and tricuspid waves) were not modified. Conclusions: Alterations of myocardial functions are observed in soldiers after uninterrupted prolonged intense exercise performed during selection boot camps. These alterations occur both in elite and non-elite soldiers. 2D-strain is more sensitive to detect EICF than conventional echocardiographic parameters.